Through the eye of the beholder: To seclude or not to seclude - Wynaden, Dianne; Chapman, Rose; McGowan, Sunita; Holmes, C.; Ash, P.; Boschman, A. (Blackwell Publishing, 2002)
ABSTRACT: The objective of this study is to provide new knowledge and understanding of the decisionmaking used throughout the seclusion process. Seven mental health nurses and one doctor were eachinterviewed within 48 hours of making the decision to seclude a patient. The interviews were analysedusing content analysis. This study provides valuable information regarding factors that are central to,and/or influence, the decision-making process surrounding seclusion. More importantly, the resultsdemonstrate that seclusion is initiated only when all other less restrictive patient management strategieshave proven to be unsuccessful with the patient.